Workplace related mental health problems – risks and prevention - Kuhn, K. (Die Psychiatrie, 2013)
A lot of work related exposures have health effects on individuals and have specific manifestations. It is the subjective evaluation of the exposure that is decisive for stress reaction. Minimizing risk factors and mental health promotion are part of preventive strategies.
Keywords: Stress; work related health risk; mental health promotion